The geographies of difference in conflating digital and offline spaces of encounter: migrant professionals’ throwntogetherness in Singapore - Bork-Hüffer, Tabea; Yeoh, Brenda S. A. (Geoforum, 2017)
This article explores the effects of people's digital coexistence on the construction of difference and feelings of aversion to or recognition of “others”. It seeks to make a theoretical contribution to works on the geographies of difference and encounter, Internet or digital geography, as well as on migration and digital media, by highlighting the relevance of indirect and fleeting digital encounters and the dialectical process in which encounters play out in intertwined, specific and multiple digital and physical spaces that we define as “cON/FFlating situational places of encounter”. Based on a qualitative study with Chinese, Filipino and German migrant professionals in Singapore, it shows how fleeting digital encounters take an ambivalent role through challenging but also producing new “temporary fixings of difference”. As such they can engender new sensibilities for and openness toward the host society but also breed new, or aggravate existing, cultural stereotypes and prejudices. The findings show that inherited and instituted classificatory practices that people use to structure and make sense of their fleeting interactions with others in offline space are, where possible, transferred and imposed on encounters in digital space. At the same time, they are inflected or replaced with new markers of difference where ingrained sorting mechanisms applied in offline space did not help them make sense of encounters in digital space.